MEDIA PUBLIKASI HUMAS DALAM PENDIDIKAN - Mahfuzhah, Hannah; Anshari, Anshari (JURNAL AL-TANZIM, 2018)
The effort to build good relations with the media is one way to make the institution's image better. Media use activities are carried out to influence the public to achieve organizational goals. Mass media is usually used by organizations or educational institutions to build the image of the institution.In order to be able to perform its functions properly, the role of public relations must be carried out by competent people in their fields. A publicist must be smart in choosing publications, so that the intent to be conveyed to the public can be appropriate and on target. Although the public relations and mass media have a mutually beneficial relationship, there are some things that need to be considered so that especially for educational institutions that have the aim of publishing educational institutions so that a good relationship between public relations and mass media is maintained.